Chitosan/Selenium Nanoparticles Attenuate Diclofenac Sodium-Induced Testicular Toxicity in Male Rats - Samy M. El-Megharbel; Fawziah A. Al-Salmi; Sarah Al-Harthi; Khadeejah Alsolami; Reham Z. Hamza (Crystals, 2021)
The detrimental effect of diclofenac sodium (Diclo-Na) on male reproductive organs is reported upon in this paper. Chitosan is a polysaccharide composed of various amounts of glucosamine. Chitosan nanoparticles (CH-NPs) have attracted much attention owing to their biomedical activity. Selenium (Se) has a vital role in nutrition, plays an important role in enhancing male reproduction, and has a wide range of free radical scavenging activities. However, the study of the impact of chitosan nanoparticles in combination with Se (IV) (CH-NPs/Se) on male reproductive toxicity associated with Diclo-Na administration is lacking in recent literature. The current study assessed the ameliorative effects of complexes of CH-NPs/Se (IV) on Diclo-Na and the ways in which they alter reproductive toxicity in male rats. Male rats were treated for 30 days successively, either with Diclo-Na (10 mg/kg) or co-treated with a CH-NPs/Se complex (280 mg/kg). Sperm characteristics, marker enzymes of testicular function, LH, FSH, and testosterone were evaluated in addition to oxidative stress markers and histological alterations. CH-NPs/Se significantly alleviated Diclo-Na-induced decline in sperm count and motility, testicular function enzymes, and levels of LH and testosterone in serum. Additionally, CH-NPs/Se co-administration at 280 mg/Kg, inhibited the Diclo-Na-induced decline of antioxidant enzyme activities and elevated oxidative stress indices and reactive free radicals in testicular homogenates of male rats. CH-NPs/Se (280 mg/kg) alone improved Diclo-Na and ameliorated histological damages in exposed rats. In conclusion, chitosan improved testicular function in Diclo-Na-treated rats by enhancing the testosterone hormone levels, ameliorating testicular tissue, and inhibiting markers of oxidative stress in male rats.